Analisis Penerapan Qawāʿid Fiqhiyyah Di Era Modern - Nova Kharisma; Berliana Andini; Sarman, Sarman; Bastami; Lisnawati (CV. ITTC INDONESIA, 2025)
This article explores the application of Qawāʿid Fiqhiyyah (Islamic legal maxims) in addressing modern-day issues, particularly in the fields of economics, healthcare, and social media. This study employs a qualitative-descriptive approach through library research involving both classical and contemporary sources. The findings indicate that Qawāʿid Fiqhiyyah serve as a flexible and relevant normative foundation to resolve contemporary legal challenges not explicitly addressed in primary Islamic texts. Legal maxims such as al-ḍararu yuzāl (harm must be eliminated) and al-umūru bi maqāṣidiha (matters are judged by their objectives) are crucial in formulating adaptable yet Sharia-compliant rulings. The study also emphasizes the importance of cautious application, recognition of exceptions, and continuity among legal maxims to ensure valid and beneficial legal outcomes.